Feedback control for noise-aided parallel micromanipulation of several particles using dielectrophoresis - Zemánek, Jiří; Michálek, Tomáš; Hurák, Zdeněk (Electrophoresis, 2015)
The paper describes a novel control strategy for simultaneous manipulation of several microscale particles over a planar microelectrode array using dielectrophoresis. The approach is based on a combination of numerical nonlinear optimization, which gives a systematic computational procedure for finding the voltages applied to the individual electrodes, and exploitation of the intrinsic noise, which compensates for the loss of controllability when two identical particles are exposed to identical forces. Although interesting on its own, the proposed functionality can also be seen as a preliminary achievement in a quest for a technique for separation of two particles. The approach is tested experimentally with polystyrene beads (50 microns in diameter) immersed in deionized water on a flat microelectrode array with parallel electrodes. A digital camera and computer vision algorithm are used to measure the positions. Two distinguishing features of the proposed control strategy are that the range of motion is not limited to interelectrode gaps and that independent manipulation of several particles simultaneously is feasible even on a simple microelectrode array.
Keywords: Equipment Design; zpětná vazba; Signal Processing, Computer-Assisted; Feedback; teoretické modely; Feedback control; počítačové zpracování signálu; hluk; mikromanipulace; Electrophoresis; Algorithms; elektroforéza; Dielectrophoresis; Electrodes; Visual feedback; algoritmy; elektrody; Parallel manipulation; design vybavení; Micromanipulation; Microspheres; Models, Theoretical; Noise; mikrosféry